ANALYSIS OF INDONESIA’S GREEN GDP ACCOUNTING WITH GREY SYSTEM THEORY TYPE GM (1,1) FOR YEARS 2000 – 2010 - Andistya Oktaning Listra (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This research aimed to measure Green GDP accounting with Grey System Theory Type GM (1,1) with a case study on Indonesia's Green GDP for years 2000 – 2010. The data used in this research is secondary data obtained from Sucofindo. Based on previous research found that Green GDP accounting which known as success indicator for green economic still encountered some disadvantages such as general equilibrium effects which not accompanied with policies and efforts to internalize natural resources and environmental cost, the difficulties to setting the price of natural resources, and unclear information about natural resources inventories due to the lack of comprehensive calculations in estimating data, especially related to the quantity, quality, and changes in natural resources. Therefore, referring to (Lu and Chiu, 2012) the researchers sought to apply Grey System Theory type GM (1,1) for Indonesia's Green GDP accounting for years 2000 – 2010 as an attempt to measure Green GDP accounting. From the results of measurements, the value of MPE and MAPE both showed bias conditions (15%) and less accurate (36.59%). Indirectly those reflect the weakness of Indonesia's Green GDP accounting.Keywords: Green GDP accounting, Grey System Theory Type GM (1,1), Weakness in Indonesia’s Green GDP accounting